2022
DOI: 10.7759/cureus.31624
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Pre-consultation Tablet-Based Questionnaire on Changes in Consultation Time for First-Visit Patients With Diabetes: A Single-Case Design Preliminary Study

Abstract: Background and objectiveIt has been reported that physicians spend about 50% of their time in the outpatient department doing nonface-to-face patient work, such as charting and desk activities. Work outside of patient consultations is often considered a burden. In this study, we aimed to examine whether the use of pre-consultation tablet-based questionnaires for first-visit diabetic patients had any impact on the time spent for consultation. MethodsThe sole participant was a diabetologist with more than 20 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…By obtaining a more detailed and accurate medical history prior to the patient's visit, healthcare providers can optimize the time spent during consultations. The same study demonstrated that the clinical time with a patient in a tablet-based group was 19 minutes and 37 seconds, while in paper-based group, it was 11 minutes 25 seconds (p=0.026) [4]. This efficiency empowers clinicians to concentrate on specific concerns, make well-informed decisions, and tailor personalized treatment plans.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…By obtaining a more detailed and accurate medical history prior to the patient's visit, healthcare providers can optimize the time spent during consultations. The same study demonstrated that the clinical time with a patient in a tablet-based group was 19 minutes and 37 seconds, while in paper-based group, it was 11 minutes 25 seconds (p=0.026) [4]. This efficiency empowers clinicians to concentrate on specific concerns, make well-informed decisions, and tailor personalized treatment plans.…”
Section: Introductionmentioning
confidence: 89%
“…Subsequently, the system of history taking has evolved and improved significantly. Pre-consultation history taking systems empower patients to complete structured questionnaires or surveys before their scheduled appointments, enabling them to carefully consider their medical history and provide comprehensive responses [4]. This approach enables patients to furnish their medical histories at their own pace, thereby reducing the likelihood of overlooking crucial details.…”
Section: Emergence and Development Of Preconsultation Systemsmentioning
confidence: 99%
See 2 more Smart Citations